(3GdNWhW GdcHQi aj GdEbJUGO GdESdGejs - (3QVG UGMH(B, (3GHh MeOs ((3YeGf(B:s (3OGQ eLOdGhj,s, 2006)
(3jVe GdGbJUGO GdGSdGej Hjf GdeTcdI GdGbJUGOjI hGdNUGFU hGdeHGOF, GdedcjI hfXegG hGdGfJGL hfXQjJg hGdfTGWGJ GdGbJUGOjI GdRQGYI hGdUfGYI hGdJLGQI hJWhQgG, GdShb aj GdacQ GdGbJUGOj GdGSdGej, WQb GdcSH GdeTQhYI aj GdGSdGe, GdQHG eagheI hCfhGYg hCKGQg, GdabQ hGKGQg aj GdaQO hGdeLJeY aj GdGSdGe, SHd eYGdLI GdabQ aj GdGSdGe, GdfbhO GdOQGge hGdOfGfjQ GdGSdGejI, HjJ GdeGd hGjQGOGJ GdOhdI GdGSdGejI, GdfabGJ GdYGeI aj GdOhdI GdGSdGejI, GdeUGQa GdGSdGejIs
(3HjHdjhZQGajG(B: (3U(B.311s
Keywords: (3GdGbJUGO GdGSdGejs; (3GdGjQGOGJ hGdfabGJs; (3GdHfhcs